Are we ready for the challenge of implementing risk-based breast cancer screening and primary prevention?. (June 2018) - Rainey, Linda; van der Waal, Daniëlle; Jervaeus, Anna; Wengström, Yvonne; Evans, D. Gareth; Donnelly, Louise S.; Broeders, Mireille J.M.
Abstract: Background: Increased knowledge of breast cancer risk factors provides opportunities to shift from a one-size-fits-all screening programme to a personalised approach, where screening and prevention is based on a woman's risk of developing breast cancer. However, potential implementation of this new paradigm could present considerable challenges which the present review aims to explore. Methods: Bibliographic databases were searched to identify studies evaluating potential implications of the implementation of personalised risk-based screening and primary prevention for breast cancer. Identified themes were evaluated using thematic analysis. Results: The search strategy identified 5699 unique publications, of which 59 were selected for inclusion. Significant changes in policy and practice are warranted. The organisation of breast cancer screening spans several healthcare delivery systems and clinical settings. Feasibility of implementation depends on how healthcare is funded and arranged, and potentially varies between countries. Piloting risk assessment and prevention counselling in primary care settings has highlighted implications relating to the need for extensive additional training on risk (communication) and prevention, impact on workflow, and professionals' personal discomfort breaching the topic with women. Additionally, gaps in risk estimation, psychological, ethical and legal consequences will need to be addressed. Conclusion: The present review identified considerable unresolved issues and challenges. Potential implementation will require a more complex framework, in which a country's healthcare regulations, resources, and preferences related to screening and prevention services are taken into account. However, with the insights gained from the present overview, countries expecting to implement risk-based screening and prevention can start to inventory and address the issues that were identified. Highlights: Implementation will impact extensively on screening practice and policy. Moratoria are required to warrant women's privacy regarding (genetic) risk data. Strategies for risk communication need to be developed to warrant informed consent. Professionals need training to determine risk-based screening and prevention advice.